ANALYSIS OF TRANSFORMATIONAL LEADERSHIP IN COMMUNITY NURSES FOR REDUCING ADOLESCENT CYBERBULLYING - Lekatompessy, Roland; Dwiantoro, Luky; Fauzan, Suhaimi (Sekolah Tinggi Ilmu Keperawatan Muhammadiyah Pontianak, 2025)
Background: The problem of cyberbullying in adolescents must be prevented and changed, because adolescents cyberbulying has a negative impact on their physical, mental, social well-being. Information from the World Health Organization (WHO), states that “the population including adolescent must have good physical, mental and social well-being, so, in realizing that, it can be done through community nurses to practice education and care, respect for human dignity, and the physical health of adolescents. Community nurses are expected to be leaders who are able to do transformational leadership to influences and inspires adolescents, develops strategies, negotiation skills, and cyberbullying victim management. Purpose: This study aimed to determine the transformational leadership style of community nurses to reducing adolescent cyberbullying. Method: The method used in this research is literature review, information searched through PubMeds, Google Schoolar, and Diponegoro Nursing Journal. Searched keywords are aldolescent cyberbullying, community nurse, transformational leadership. Result: Transformational leadership of community nurses for adolescents cyberbullying provides benefits such as providing emotional support to adolescents so that adolescents are able to have change their life to be better, This result is carried out through supporting the development of positive youth skills and assisting adolescents in achieving the desired results, stimulating adolescent intellectuals, inspiring adolescents, instilling pride, mutual respect and having trust in adolescents and their families. Conclusion: Transformational leadership in community nurses has benefits to providing support and motivation, caring, and give better life such as positif or adaptive behaviour to adolescents who experience cyberbullying.